Review of multicast QoS routing protocols for mobile ad hoc networks - Hassan Abdalla Hashim, Aisha; Qabajeh, Mohammad M.; Khalifa, Othman Omran; Qabajeh, Liana K. (IJCSNS, 2008)
A Mobile Ad hoc NETwork (MANET) is consisting of a collection of wireless mobile nodes, which form a temporary network without relying on any existing infrastructure or centralized administration. Since the bandwidth of MANETs is limited and shared between the participating nodes in the network, it is important to efficiently utilize the network bandwidth. Multicasting can minimize the link bandwidth consumption and reduce the communication cost by sending the same data to multiple participants. Multicast service is critical for applications that need collaboration of team of users. Multicasting in MANETs becomes a hot research area due to the increasing popularity of group communication applications such as video conferencing and interactive television. Recently, multimedia and group-oriented computing gains more popularity for users of ad hoc networks. So, effective Quality of Service (QoS) multicasting protocol plays significant role in MANETs. In this paper, we are presenting an overview of set of the most recent QoS multicast routing protocols that have been proposed in order to provide the researchers with a clear view of what has been done in this field.